HISTORICAL AND COMPARATIVE DEVELOPMENT OF LIBRARIANSHIP IN THE SAMARKAND REGION DURING THE SOVIET PERIOD (1917–1991) - Jiyanbekova Sharofat Abdikaxarovna (Science, education, innovation: modern tasks and prospects, 2025)
This paper explores the historical development of librarianship and library institutions in the Samarkand region of Uzbekistan during the Soviet period (1917–1991), offering a comparative overview with other regions of the Uzbek SSR. It highlights key phases in library expansion, the institutionalization of educational libraries, children’s library systems, and the professionalization of librarianship. Through archival sources, historical newspapers, and scholarly studies, the paper analyzes how Samarkand emerged as a key regional hub for library innovation in Soviet Central Asia.